Analisis Permintaan Wisatawan Millennial Terhadap Obyek Wisata Sungai Koran Melalui Faktor Sosioekonomi dan Lokasi - Indra, Muh; Irawan, _; Nababan, Vera Monica (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to determine the effect of socioeconomic factors (age, age, and income) and factors related to location (cost and distance) of millennial tourists. This type of research is explanations and field surveys with a sample non-probability technique of 150 respondents. The analysis technique uses multiple linear regression. The results showed that the cost of travel, age of income and distance had a positive and significant effect on the number of millennial tourists visiting the attractions of the Sungai Koran Park, Sebangau National Park. The implication of this study is the development of the tourism infrastructure of the Koran River as one of the national tourism destinations to the Province of Central Kalimantan.